DETERMINATION OF ELEMENTAL IMPURITIES IN SOME COMMERCIAL PAEDIATRIC AND ADULT FORMULATIONS OF ARTEMETHER – LUMEFANTRINE IN THE NIGERIAN MARKET BY ATOMIC ABSORPTION SPECTROSCOPY - Awofisayo, Sunday O; Okhamafe, Augustine O; Arhewoh, Mathew I (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
The composition of elemental impurities in paediatric powder for suspension (PPS) and double strength tablet (DST) commercial anti-malarial formulations of artemether-lumefantrine (AL) were determined. Six randomly selected PPS and DST products from a list of marketed products were purchased from a registered Pharmacy outlet and analyzed using flame atomic absorption spectrophotometer. The heavy metal levels were compared with the official limits for permitted daily exposure. The paediatric and adult products of AL presented the same types and number of elements with a total of 10 metals and levels ranging from 0.001-0.016 and 0.001-0.017ppm for the PPS and DST formulation, respectively. One of the DST and PPS products had significantly higher levels of cadmium, copper, chromium, nickel and cobalt compared with their respective formulation types (p<0.05). There was significant difference in the levels of chromium, nickel and cobalt but no difference in the levels of cadmium, lead, zinc and arsenic when DST and PPS products were compared (p<0.05). The drug products presented elemental oral exposure significantly lower than the permitted daily exposure. The levels of elemental impurities are satisfactory with respect to safety requirements. These impurities may adversely affect drug stability, shelf-life and bioequivalence of the products.Key words: Elemental impurities, Permitted Daily Exposure, Artemether-lumefantrine, Paediatric Powder for Suspension, Double Strength Tablets